Feeding and the Rhodopsin Family G-Protein Coupled Receptors in Nematodes and Arthropods - Cardoso, Joao C.; Felix, Rute C.; Fonseca, Vera G.; Power, Deborah M. (Frontiers in Endocrinology, 2012)
In vertebrates, receptors of the rhodopsin G-protein coupled superfamily (GPCRs) play an important role in the regulation of feeding and energy homeostasis and are activated by peptide hormones produced in the brain-gut axis. These peptides regulate appetite and energy expenditure by promoting or inhibiting food intake. Sequence and function homologues of human GPCRs involved in feeding exist in the nematode roundworm, Caenorhabditis elegans (C. elegans) and the arthropod fruit fly, Drosophila melanogaster (D. melanogaster), suggesting that the mechanisms that regulate food intake emerged early and have been conserved during metazoan radiation. Nematodes and arthropods are the most diverse and successful animal phyla on Earth. They can survive in a vast diversity of environments and have acquired distinct life styles and feeding strategies. The aim of the present review is to investigate if this diversity has affected the evolution of invertebrate GPCRs. Homologues of the C. elegans and D. melanogaster rhodopsin receptors were characterized in the genome of other nematodes and arthropods and receptor evolution compared. With the exception of bombesin receptors (BBR) that are absent from nematodes, a similar gene complement was found. In arthropods, rhodopsin GPCR evolution is characterized by species-specific gene duplications and deletions and in nematodes by gene expansions in species with a free-living stage and gene deletions in representatives of obligate parasitic taxa. Based upon variation in GPCR gene number and potentially divergent functions within phyla we hypothesize that life style and feeding diversity practiced by nematodes and arthropods was one factor that contributed to rhodopsin GPCR gene evolution. Understanding how the regulation of food intake has evolved in invertebrates will contribute to the development of novel drugs to control nematodes and arthropods and the pests and diseases that use them as vectors.